The Effects of Blooket on Motivation in Learning English among First-Year Non-English Majors at A University in Ho Chi Minh City - PHUC LUONG HUYNH, DIEM (International Journal of English Language Education, 2024)
This study reviews Blooket's impacts on 51 non-English major university students' vocabulary and reading skills through their intrinsic and extrinsic motivation in comparing when teachers use traditional and technological methods in teaching based on Ryan and Deci's self-determination framework (2020). The research conducted by Shliakhtina et al. (2023) has indicated that old-fashioned approaches, like the Grammar Translation Method with appropriate teacher support, can also enhance students' motivation. However, students sometimes need more support learning vocabulary and reading skills because it is a learned-by-heart process. The study gathered data on students' motivation levels when exposed to different teaching approaches by conducting action research. This data can help identify the effectiveness of Blooket in enhancing students' intrinsic and extrinsic motivation, according to the research of Tran (2022) and Thu & Dan (2023). The results indicate that incorporating elements of extrinsic motivation, such as points or badges within Blooket, also contributes to overall motivation. Students may feel a sense of achievement and be further motivated to participate actively in language learning activities. The interactive nature of Blooket, along with its ability to create a supportive learning environment, fosters a sense of learning and self-awareness among learners. This, in turn, allows students to understand their strengths and weaknesses and take ownership of their learning process.